The usage of KiplePay among students in Kachi Mall - Zainon, Nur Azmina; Mohd Zamani, Siti Norhasmaedayu (Universiti Utara Malaysia, 2020)
In this sophisticated era, smart phones have turned into a significant part in daily life especially among students. In Universiti Utara Malaysia, students are offered this e-wallet app which is KiplePay to be used, yet there are some students that may be still not aware and unsatisfied with KiplePay. Thus, in this study attempts to identify the level of awareness and usage towards KiplePay among students plus the factors affect student satisfaction towards KiplePay. This study is a quantitative research. A survey has been distributed to all Bukit Kachi students who used KiplePay with filtered and required every question to be answered to avoid missing data. The findings are measured to support the hypotheses or else. The reliability of data and structural model for hypotheses has been tested. The findings gained in this study may be helpful for KiplePay providers to improve the app to be more efficient and well acknowledged among the students in Universiti Utara Malaysia.